Gender and access to bank credit around the world during the COVID-19 pandemic: The mediating role of digital transformation - Safiullah Khan; Ulaganathan Subramanian; Pg Abdul Mutalib (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
Drawing on the rich firm-level enterprise survey dataset of more than 58,000 small enterprises in 39 developing and emerging economies, this study investigates gender disparities in firms' financial fragility, credit demand, and credit provision during the COVID-19 pandemic, and the role of digital transformation in addressing these disparities. We used a probit model with selection and an instrumental variable approach to account for the selection effects and endogeneity of the female ownership and leadership measures. Furthermore, several robustness checks are used to account for endogeneity problems caused by omitted variables and self-selection bias. These econometric tests were conducted using STATA software. We find that female-led businesses are more vulnerable to the negative effects of the pandemic and have higher demand for credit. However, they are less likely to request loans (credit self-rationing) and more likely to be denied credit when applying for bank credit. This gender bias in credit provision is exacerbated by the pre-pandemic financial constraints on female-led enterprises. This study also tested the mediating role of a firm's technology adoption and digital transformation in credit access. The results of the mediation analysis show that female-led enterprises that adopted ecommerce and remote work technologies during the pandemic had better access to bank credit than other firms, suggesting that digital transformation significantly enhanced female-led businesses' access to bank credit and narrowed gender disparities in the credit market in times of extreme financial and economic distress.
Keywords: 330; Digital transformation; e-commerce; gender and bank credit access; financial constraints; borrower discouragement; financial inclusion